How The Residents Are Affected from Construction Operations Conducted in Residential Areas - Celik, Tolga; Budayan, Cenk (Elsevier Science Bv, 2016)
The construction projects have adverse impacts on the residents who live at a neighborhood of a construction project. In the literature, these adverse impacts are identified and the social cost of these adverse impacts are formalized. However, in all these studies, all adverse impacts are assumed to create nuisance at the same level, whereas the residents are more sensitive to some of these nuisances, on the other hand some of the nuisances which are considered in the social cost studies can be overlooked by the residents, and therefore this can cause misleading calculations of social cost. In order to overcome shortcoming of social cost studies, a study, which aims to identify the level of effects of each nuisance on the residents, is conducted by performing a questionnaire survey. 266 respondents are obtained at the end of the study, and the data obtained by questionnaire survey is analyzed by using descriptive analysis. According to this analysis, loss of peace and quietude of the neighborhood, cleanliness of the house, and degradation of ambient conditions are identified as the most disturbing nuisances. In addition, the country conditions and culture of the region is considered as important factors that play an important role in the intensity of adverse impacts. (C) 2016 The Authors. Published by Elsevier Ltd.
World Multidisciplinary Civil Engineering-Architecture-Urban Planning Symposium (WMCAUS) -- JUN 13-17, 2016 -- Prague, CZECH REPUBLIC
Keywords: Adverse Impacts; Stakeholder Management; Criticality Index